Future Energy Source for Remote IoT Systems using MEMS-based Piezoelectric Energy Harvesting Devices. Issue 1 (August 2021) - Fareeza, F.; Krishna Veni, S.; Rambabu, Chunchu; Yanore, Tigabu Zewude; Rajkumar, P.
Abstract: Piezoelectric energy harvesting (PEH) device is an energy converter that will convert mechanical vibration energy into electrical energy. The energy converter is implemented using Micro-Electronic Mechanical System (MEMS). The vibration is extracted from the surroundings, and the extracted vibration is converted into electrical energy using PEH for low power sensors used in the IoT environment. PHE device will generate the maximum power when the vibration of the surrounding is exactly matched with the resonant frequency of the device. This paper presents two different PHE MEMS devices which will convert the vibration into electrical energy. The proposed device has two design materials; T shape resonant model is designed by arranging beams in multilayer and an ultra-violet resin seismic mass. There are four-layer formed together; the substrate first layer is built using polyethylene terephthalate (PET). The third layer is formed by using piezo-electric material; the second and fourth layers are build using aluminium and platinum electrode. In the model, two different types of piezoelectric materials are used to build the PEH device. Two types of material used in the devices are ZnO and PZT-5A. Rayleigh-Ritz and Macaulay methods are used to model the system for analysing the mechanical behaviour of the model and structural analysis for the better energy extraction using FEM. The proposed PHE device using ZnO and PZT-5A is generating power at the rate of 1.8 W and 1.35 W with a voltage rating of 545 and 45 mV, respectively. The Proposed PHE device is built for remote location low power IoT devices.